2020
DOI: 10.1177/1558944719895622
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Sagittal Band Injuries and Extensor Tendon Subluxation: A Systematic Review

Abstract: Background: This systematic review assesses the current literature and reviews the clinical outcomes of treatment for sagittal band injuries and extensor tendon instability. Materials: A systematic search of MEDLINE, EMBASE, and the Cochrane databases was performed for English-language articles on the treatment of nonrheumatoid adult sagittal band injuries between 1969 and 2019. Two independent reviewers were involved in screening, data extraction, and critical appraisal. The level of evidence was assigned usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Posner & Ambrose later reported the injury in six professional athletes, and nearly all patients attained a full range of motion postoperatively [9]. The authors noted that accompanying extensor tendon subluxation resulted in more severe cases, a finding supported by a subsequent case series [10,11]. Our patient presented similarly with dynamic subluxation of the extensor tendon into the groove between the third and fourth digits with ulnar deviation of the long finger.…”
Section: Sagittal Band Ruptures and Managementsupporting
confidence: 67%
See 1 more Smart Citation
“…Posner & Ambrose later reported the injury in six professional athletes, and nearly all patients attained a full range of motion postoperatively [9]. The authors noted that accompanying extensor tendon subluxation resulted in more severe cases, a finding supported by a subsequent case series [10,11]. Our patient presented similarly with dynamic subluxation of the extensor tendon into the groove between the third and fourth digits with ulnar deviation of the long finger.…”
Section: Sagittal Band Ruptures and Managementsupporting
confidence: 67%
“…In contrast, type IV injuries typically require surgery [ 13 ]. Successful non-surgical management has been reported in the literature: Ritts et al utilized dorsal splinting in two patients with sagittal band ruptures, Catalano et al treated ten patients with a digital extension orthosis referred to as a sagittal band bridge, and Wu et al found nonoperative management to be a successful approach in injuries presenting within three weeks [ 11 , 14 , 15 ]. Our patient presented with a type IV rupture based on the presence of extensor tendon subluxation at his initial visit, three months following his injury.…”
Section: Discussionmentioning
confidence: 99%
“…Dislocation of extensor tendons involves displacement of the tendon into the groove between adjacent dorsal MC heads (valley between adjacent knuckles) and loss of contact with the dorsal aspect of the metacarpal head. 16,32 In When complete sagittal band tears occur to the second and fifth MCPJs, due to the presence of multiple tendons, ruptures of the connections between these tendons have been identified to also occur and one of the extensor tendons may displace to the radial side and one to the ulnar side of the MC head relative to midline. 19 The radial sagittal band is reported to be more susceptible to injury; this theory has been proposed as the radial sagittal band has been identified to be thinner and longer than the ulnar component on cadaveric studies.…”
Section: Sonographic Imaging Of Sagittal Band Tearsmentioning
confidence: 99%
“…Transient subluxation of the extensor tendon with flexion involves maintenance of contact of the tendon with the dorsal metacarpal condyle. Dislocation of extensor tendons involves displacement of the tendon into the groove between adjacent dorsal MC heads (valley between adjacent knuckles) and loss of contact with the dorsal aspect of the metacarpal head 16,32 . In complete sagittal band tears of the third and fourth MCPJs, ED tendon dislocation occurs when the tendon moves to the opposite side of the MC head relative to the side of the sagittal band tear.…”
Section: Sonographic Imaging Of Sagittal Band Tearsmentioning
confidence: 99%
“…EDC subluxation may present with a trauma history[ 20 ] in cases of sagittal band rupture, but may also have a spontaneous onset[ 20 ] in cases of sagittal band attrition[ 10 ]. The MCPJ will generally be swollen and tender dorsally with clicking (pseudo triggering)[ 10 ] noted during motion[ 11 ].…”
Section: Diagnosismentioning
confidence: 99%